Poder e trabalho : análise dos programas de ressocialização de apenadas do estado do Espírito Santo - Lopes, Beatriz Correia (2013)
Considering the reality of Brazilian prison, especially of the state of Espírito Santo, the object of this study, the increase in the percentage of incarcerated women in the state and the massive deployment of resocialization programs in penal institution